The efficacy and safety of chemoimmunotherapy in patients with MSI-L/MSS/pMMR status metastatic colorectal cancer: a systematic review and meta-analysis of randomized controlled trials - Qi-Jing Zhang; Qi-Jing Zhang; Jia-xin Zhou; Jia-xin Zhou; Da-hai Hu; Jing-hua Pan; Jing-hua Pan; Si-min Luo; Si-min Luo; Qi Yao (Frontiers in Oncology)
BackgroundColorectal cancer (CRC) remains a leading cause of cancer-related mortality worldwide, necessitating innovative therapeutic approaches. Most patients with CRC exhibit microsatellite instability-low/stable (MSI-L/MSS) or proficient mismatch repair (pMMR) status, with chemotherapy being the standard first-line treatment. Chemoimmunotherapy, incorporating immune checkpoint inhibitors (ICIs), has emerged as a potential treatment for MSI-L/MSS/pMMR CRC. This study aimed to comprehensively evaluate the efficacy and safety of chemoimmunotherapy in metastatic CRC (mCRC) patients with MSI-L/MSS/pMMR status.MethodsA systematic search of PubMed, EMBASE, ScienceDirect, and Cochrane Library was conducted in accordance with PRISMA guidelines, targeting studies published between May 2022 and September 2024. The meta-analyses utilized the generic inverse-variance method with a random effects model.ResultsFour studies encompassing 934 patients with mCRC met the inclusion criteria. The meta-analysis revealed a significant reduction in the risk of progression or death with chemoimmunotherapy compared with chemotherapy (HR: 0.82, 95% CI: 0.70–0.97, P = 0.02). Subgroup analyses based on sex (male vs. female) and ECOG status consistently demonstrated a significant benefit of chemoimmunotherapy in MSI-L/MSS/pMMR tumors. Adverse event analysis indicated an increase in adverse events in the chemoimmunotherapy group.ConclusionExisting evidence indicates a statistically significant and clinically meaningful benefit in PFS with chemoimmunotherapy, albeit with a slight increase in all-grade and high-grade toxicities compared to chemotherapy. Future research focusing on biomarkers and innovative treatments is essential for enhancing patient outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024520150.